IMPROVING INVESTMENT FINANCIAL MANAGEMENT METHODOLOGY (Marketing Journal, 2025)
This article examines the current state of financial management of investments, the specific features of managing investment processes through regulating investment attractiveness in the economy, as well as the development of a methodology for determining the required level of investment needed to ensure sustainable economic growth, including the analysis of the factors influencing this process. In addition, the article presents conclusions based on the research results, along with proposals and recommendat ions of scientific and practical significance.
Keywords: financial investment management; syndicated loan; foreign experience; investment attractiveness; venture capital; venture capital market; investment companies; investment funds; capital investments. 559